The Goodness for All: An Exploration of Matthew 4:45 and Its Implementation for Church Ministry - Sukanto Limbong (International Journal on Advanced Science, Education, and Religion, 2024)
This introduction aims to provide a general overview of the research topic, namely the exploration of Matthew 4:45 and its implementation for church services. Readers will be introduced to the aim and scope of the research, as well as the importance of understanding the concept of goodness in a biblical context. Matthew 4:45 is part of the Gospel of Matthew in the Bible, which presents the story of the ministry of Jesus Christ in the world. Exploration of this text will provide a deeper understanding of the teachings and stories contained in this chapter, so that they can be applied in the current context of Christian life, especially in church ministry. A qualitative approach was applied in this research to explore the principle of kindness in the context of church service. In conducting this research, researchers will be involved in participant observation and in-depth interviews with church leaders and congregation members. Qualitative data will be collected through field notes, interview transcriptions, and content analysis to identify themes and patterns related to the concept of goodness in Matthew 4:45. In this research, it was found that the principle of goodness explained in Matthew 4:45 has significant implications for church ministry. These implications include the importance of building a church community that supports and cares for each other, as well as encouraging the practice of love and mercy in every aspect of church life. In addition, this research also highlights the need to pay attention to historical and cultural contexts in interpreting and applying the principle of goodness in church services to make them relevant and effective.